The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21708/avb.2021.15.3.9421
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of pâté using fish residues

Abstract: Knowing the potential of fish waste for the preparation of pâtés, there is the possibility of adding greater sustainability to the aquaculture sector. The aim was to prepare pâtés from fish processing residues with the inclusion of smoked fishmeal and evaluate their sensory, microbiological, physicochemical, and shelf-life characteristics. Three treatments were used: pâté without fishmeal inclusion (PSF), with smoked salmon carcass meal inclusion (PFSD), and smoked tilapia car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…In this independent study of the fish region, the longitudinal direction showed greater elasticity, with the head region being significantly the highest stretching value 95.80%. These results corroborate with Matiucci et al 1,2 who reported that Nile tilapia leather in the longitudinal direction has greater elasticity compared to transverse direction of the leather in this fish species. However, it is possible that the leather demonstrates different results, even if the leathers are from same species of fish and are evaluated in the same directions as the leather.…”
Section: Test 1: Physicomechanical Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…In this independent study of the fish region, the longitudinal direction showed greater elasticity, with the head region being significantly the highest stretching value 95.80%. These results corroborate with Matiucci et al 1,2 who reported that Nile tilapia leather in the longitudinal direction has greater elasticity compared to transverse direction of the leather in this fish species. However, it is possible that the leather demonstrates different results, even if the leathers are from same species of fish and are evaluated in the same directions as the leather.…”
Section: Test 1: Physicomechanical Characteristicssupporting
confidence: 91%
“…The generation of by-products within a processing line of an industry has become a growing concern among consumer population and generate concern in industries due to correct form of disposal and how to obtain the better use of the raw material. 1 According to Matiucci et al, 2 among by-products generated, about 4.5 to 10% represent the fish skin. Variation in this number of by-products depends on the species and way in which it is removed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with the purpose of attracting investors, research has been developed every year, making the pet market an attractive option for business opportunities (Mazon & Moura, 2017). In Brazil, the population is increasingly appreciating and investing in their animals, for example with toys, baths and grooming and snacks (Matiucci et al, 2020(Matiucci et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…11 Furthermore, the residue from fish processing can be used for better use in several alternative lines in the consumer market, such as: pet feeds, fertilizers for agriculture and gardening, agrochemicals, immunomodulators, oil rich in n-3, human food (fishpâtét and mechanically separated -MSM prepared by the processing unit), including biodiesel extraction processes and other value-added products. 10,12 The optimized use of these products from the food industry is a great alternative to reduce the lack of animal products rich in proteins and at the same time composed of healthy fats.…”
Section: Introductionmentioning
confidence: 99%